A technique for the capture of free-ranging marsh deer (blastocerus dichotomus) - Duarte, Jose Mauricio Barbanti [UNESP] (Amer Assoc Zoo Veterinarians, 2008)
The marsh deer (Blastocerus dichotomus) is an endangered species froth the marshlands of central South America. Its population has declined in several regions due to the loss of available habitat caused by human activities, especially the construction of hydroelectric darns. The capture of individual deer is critical for research programs and population management. This report describes a novel live-capture technique, which uses a helicopter to drive the animals into a terrain that restricts their movement such as thick vegetation or deep water (60-120 cm in depth). Following confinement, animals are manually restrained. The short pursuit time (median = 2 thin), low mortality rate (0.82-3.28%), and the absence of injury to both the capture team and animals suggest that this method is appropriate for the safe capture of this species. Body temperature correlated with the pursuit time (R-2 = 0.15) but was not significantly altered with pursuit times <3 min.
Keywords: Blastocerus dichotomus; Brazil; Capture; Cervidae; manual restraint; Marsh deer